Strategi Komunikasi Pengasuh Asrama Dalam Penguasaan Bahasa Asing Santri di Pondok At-Tibyan Tanjung Morawa Deli Serdang Sumatra Utara - Muhammad Ikhsan; Junaidi; Irham Dongoran (PT. Hasba Edukasi Mandiri, 2025)
This research aims to identify the communication strategies used by dormitory caregivers in facilitating the mastery of foreign languages ​​by students at the At-Tibyan Tanjung Morawa Islamic Boarding School, Deli Serdang, North Sumatra. This research also aims to analyze the factors that influence the implementation of these communication strategies in the Islamic boarding school environment. The research method used is qualitative with a descriptive approach. Data collection techniques used include observation, interviews and documentation. The findings show that the At-Tibyan Islamic Boarding School is not only an educational institution that shapes character and morality, but also a place where the younger generation can master world knowledge through mastering foreign languages. The communication strategies implemented by the dormitory caregivers have proven to be effective and have resulted in students' achievements in the field of language. However, dormitory caregivers continue to carry out evaluations to correct deficiencies in language mastery.